2010
DOI: 10.1016/j.ejcnurse.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences with symptoms and needs in the early rehabilitation phase after coronary artery bypass grafting

Abstract: CABG patients' experiences indicate a need to extend the hospital's discharge care to the first month after surgery for specific themes to promote rehabilitation outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 42 publications
4
71
0
3
Order By: Relevance
“…Lack of good sleep and chest pain were the main causes of fear of mass communication. Similarly, tiredness or fatigue, such as the need to rest or sleep during the daytime, and difficulties with sleep patterns were reported as problems, as were falling asleep or waking up too early, in Lie et al's study (10). Furthermore, the main findings of Schou and Egerod's results relate to general phenomena such as discomfort and impaired communication (28).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Lack of good sleep and chest pain were the main causes of fear of mass communication. Similarly, tiredness or fatigue, such as the need to rest or sleep during the daytime, and difficulties with sleep patterns were reported as problems, as were falling asleep or waking up too early, in Lie et al's study (10). Furthermore, the main findings of Schou and Egerod's results relate to general phenomena such as discomfort and impaired communication (28).…”
Section: Discussionmentioning
confidence: 81%
“…In line with these findings, Tolmie and colleagues found that some patients were not taking their medicines and that one of the reasons for this was that they were not convinced that their diagnosis was accurate or that the medication was necessary (30). Similarly, 35% of the patients in Lie et al's study did not know why they had to take the prescribed medication (10). In addition to the above, Shafipour et al reported that all the patients in their study requested the necessary information and education about how to use food and their medicine (13).…”
Section: Taking Medications Multiple Timesmentioning
confidence: 88%
See 2 more Smart Citations
“…Second, a comparison of studies of coronary heart disease (CHD) and the post-treatment needs of people with CRC suggests that there is reasonable justification for referring CRC patients to cardiac rehabilitation and running mixed classes involving people with CHD and people with cancer. Four qualitative studies of patients' experiences of needs after coronary artery bypass graft (CABG), [52][53][54][55] one case note review of needs of 521 patients surgically treated for CRC cancer 56 and one population-based cohort study including 522 people with CRC 57 all indicate that people with CHD and people diagnosed with CRC experience similar problems, including pain, fatigue, anxiety and depression, worry, appetite loss, sexual problems, sleep disturbance, and work and financial-related difficulties, and express a need for information about medication and self-management. Thus, the rehabilitation needs of people with CHD and those of people with CRC are likely to be similar, suggesting that a common rehabilitation programme may be appropriate.…”
Section: Physical Activity and Psychosocial Outcomesmentioning
confidence: 99%